2019
DOI: 10.1001/jamainternmed.2019.1483
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Electronic Cigarette Use and Smoking Reduction in France

Abstract: IMPORTANCEThe electronic cigarette (EC) has become popular among smokers who wish to reduce their tobacco use levels or quit smoking, but its effectiveness as a cessation aid is uncertain.OBJECTIVE To examine the association of regular EC use with the number of cigarettes smoked per day, smoking cessation among current smokers, and smoking relapse among former smokers. DESIGN, SETTING, AND PARTICIPANTSThe CONSTANCES (Consultants des Centres d'Examens de Santé) cohort study, based in France, began recruiting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 60 publications
(138 reference statements)
2
48
0
1
Order By: Relevance
“…to take up smoking or to relapse. This may con rm other studies on the greater likelihood of relapse (47) or taking up smoking among younger populations (12). However, as a caveat, for never-smoking, non-EC-users at t1 who smoked and vaped at t2, we do not know which habit began rst.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…to take up smoking or to relapse. This may con rm other studies on the greater likelihood of relapse (47) or taking up smoking among younger populations (12). However, as a caveat, for never-smoking, non-EC-users at t1 who smoked and vaped at t2, we do not know which habit began rst.…”
Section: Discussionsupporting
confidence: 85%
“…Findings from the same study (46) showed that at least high frequency of EC use at follow-up (but no use at baseline) may be associated with a reduction in CCs smoked. A general population study in France examined daily smokers and former daily smokers (47). After two years, regular (daily) vapers had reduced their daily CC use by about 1.7 cigarettes per day more than non-vapers.…”
Section: Introductionmentioning
confidence: 99%
“…In England in 2019, vaping devices were used in 31.9% of quit attempts, followed by NRT over‐the‐counter (13.7%), varenicline (4.4%) and prescribed NRT (4%) . In France since 2010, 27% of smokers who tried to quit used vaping compared to 18% who used NRT .…”
Section: Is There Enough Vaping To Influence Population Smoking Rates?mentioning
confidence: 99%
“…Sixty-seven percent more e-cigarette users than non-users quit smoking altogether. However, there were 70% more relapses among former smokers who used e-cigarettes than among those who did not use the devices [8].…”
Section: Introductionmentioning
confidence: 92%